THE INFLUENCE OF AGREEABLENESS, CONSCIENTIOUSNESS, EXTRAVERSION AND OPENNESS TO EXPERIENCE ON GREEN PURCHASE INTENTION LOVE BEAUTY AND PLANET PRODUCTS FOR STUDENTS MALIKUSSALEH UNIVERSITY. - Aprida Hanum; Halida Bahri; Widyana Verawaty Siregar; Rahmaniar (International Journal of Social Science, Educational, Economics, Agriculture Research and Technology (IJSET), 2024)
This research aims to determine the influence of Agreeableness, Conscientiousness, Extraversion and Openness to Experience on Green Purchase Intention for Love Beauty and Planet Products among Malikussaleh University Students. This research was conducted on Malikussaleh University students who used or had purchased Love Beauty and Planet products. The data used in this research is primary data obtained by distributing questionnaires directly to 100 respondents. The data analysis technique used is multiple linear regression analysis using SPSS software. The research results show that Agreeableness has a positive and significant effect on Green Purchase Intention, Conscientiousness has a positive and significant effect on Green Purchase Intention, Extraversion has a positive and significant effect on Green Purchase Intention and Openness to Experience. positive and significant effect on Green Purchase Intention.